The Interaction of Nutrition and Health in Beef Cows - Matt Hersom (EDIS)
In cattle, all physiological processes in the body, including the immune system, are influenced by the cattle’s nutritional status. Therefore, the past and present nutritional status serves as an immune function modulator in cattle that can influence the performance and reproduction of beef cattle. This 6-page fact sheet was written by Matt Hersom and published by the UF Department of Animal Sciences, June 2014.